Paranode Abnormalities and Oxidative Stress in Optic Nerve Vulnerable to Secondary Degeneration: Modulation by 670 nm Light Treatment - Szymanski, C.R.; Chiha, W.; Morellini, N.; Cummins, N.; Bartlett, C.A.; Doig, R.L.O.; Savigni, D.L.; Payne, S.C.; Harvey, A.R.; Dunlop, S.A.; Fitzgerald, Melinda (PUBLIC LIBRARY SCIENCE, 2013)
Secondary degeneration of nerve tissue adjacent to a traumatic injury results in further loss of neurons, glia and function, via mechanisms that may involve oxidative stress. However, changes in indicators of oxidative stress have not yet been demonstrated in oligodendrocytes vulnerable to secondary degeneration in vivo. We show increases in the oxidative stress indicator carboxymethyl lysine at days 1 and 3 after injury in oligodendrocytes vulnerable to secondary degeneration. Dihydroethidium staining for superoxide is reduced, indicating endogenous control of this particular reactive species after injury. Concurrently, node of Ranvier/paranode complexes are altered, with significant lengthening of the paranodal gap and paranode as well as paranode disorganisation. Therapeutic administration of 670 nm light is thought to improve oxidative metabolism via mechanisms that may include increased activity of cytochrome c oxidase. Here, we show that light at 670 nm, delivered for 30 minutes per day, results in in vivo increases in cytochrome c oxidase activity co-localised with oligodendrocytes. Short term (1 day) 670 nm light treatment is associated with reductions in reactive species at the injury site. In optic nerve vulnerable to secondary degeneration superoxide in oligodendrocytes is reduced relative to handling controls, and is associated with reduced paranode abnormalities. Long term (3 month) administration of 670 nm light preserves retinal ganglion cells vulnerable to secondary degeneration and maintains visual function, as assessed by the optokinetic nystagmus visual reflex. Light at a wavelength of 670 nm may serve as a therapeutic intervention for treatment of secondary degeneration following neurotrauma. © 2013 Szymanski et al.